2022
DOI: 10.1186/s12889-022-13061-8
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime impact of being underweight or overweight/obese during childhood in Vietnam

Abstract: Background There is limited evidence about lifetime burden of child malnutrition. This study aimed to estimate the lifetime impact of being underweight or overweight/obese during childhood in Vietnam. Methods We developed a life table model in combination with a Markov model for Vietnamese children aged 5–19 years and simulated until they reached 75 years of age or died using published data. The starting year was 2019 and the model estimated number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…In Vietnam, recent studies have shown that the incidence of AP is increasing with socioeconomic development, particularly HTG-AP [ 14 , 20 ]. The rise in HTG-AP cases is attributed to the changes in lifestyle and dietary habits that have accompanied the country’s rapid economic growth, as well as the increased prevalence of obesity, which is a known risk factor for HTG-AP [ 21 ]. The consumption of alcohol and smoking, which are also risk factors for AP, have also increased among the Vietnamese population [ 22 ], further contributing to the increase in AP cases.…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, recent studies have shown that the incidence of AP is increasing with socioeconomic development, particularly HTG-AP [ 14 , 20 ]. The rise in HTG-AP cases is attributed to the changes in lifestyle and dietary habits that have accompanied the country’s rapid economic growth, as well as the increased prevalence of obesity, which is a known risk factor for HTG-AP [ 21 ]. The consumption of alcohol and smoking, which are also risk factors for AP, have also increased among the Vietnamese population [ 22 ], further contributing to the increase in AP cases.…”
Section: Introductionmentioning
confidence: 99%